Developing Embedded Systems for E-Bike Rentals with Logistic Map-Based Token Generation - Ahmad Juniar; Al Kautsar Permana; Finna Suroso; Gita Mustika Rahmah; Muchamad Taufiq Anwar (CommIT (Communication and Information Technology) Journal, 2026)
The research presents a novel electric bike rental system that operates efficiently without an internet connection. The system integrates a logistic map algorithm into an embedded microcontroller and a web-based rental information system. The logistic map has pseudo-random code generation properties, allowing identical activation tokens to be generated on both the server and the embedded system, enabling robust token validation on e-bike units. Users rent e-bikes by scanning a barcode on the e-bike unit. The barcode then directs the user to a web interface, where they can select the rental duration via a secure payment gateway. The rental system is pay-per-use, eliminating the need for deposits or account registration and enhancing user convenience. Once payment is verified, a message is sent containing the receipt details and an activation token that can be used on the e-bike. The obtained token generation and verification times are 0.68 ms and 0.72 ms, respectively. This test demonstrates the ability to generate tokens in real time without significant latency. However, this approach faces practical issues of token collisions and hardware limitations. Token collisions occur when a 9-digit token appears twice across five different ID tokens, with counters ranging from 1 to 10,000 for the same e-bike ID and rental duration. Rounding to significant digits causes this problem due to the microcontroller’s inherent limitations. However, these duplications occur at widely separated counters, making them difficult to exploit. This system effectively balances simplicity, security, and scalability for local e-bike sharing services.